2009
DOI: 10.1107/s0021889809023553
|View full text |Cite
|
Sign up to set email alerts
|

Slow cooling of protein crystals

Abstract: Cryoprotectant-free thaumatin crystals have been cooled from 300 to 100 K at a rate of 0.1 K s À1 -10 3 -10 4 times slower than in conventional flash coolingwhile continuously collecting X-ray diffraction data, so as to follow the evolution of protein lattice and solvent properties during cooling. Diffraction patterns show no evidence of crystalline ice at any temperature. This indicates that the lattice of protein molecules is itself an excellent cryoprotectant, and with sodium potassium tartrate incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 55 publications
3
53
0
1
Order By: Relevance
“…However, these temperatures are of the greatest interest for understanding radiation-damage mechanisms because near T = 200 K the protein and solvent system undergoes a dynamical/glass transition (Parak et al, 1982;Doster et al, 1989;Weik et al, 2001Weik et al, , 2004Weik et al, , 2005Gabel et al, 2002). The present study was made possible by the methods and observations described in detail by Warkentin & Thorne (2009), which were in turn inspired by earlier investigations (Weik et al, 2001(Weik et al, , 2005Juers & Matthews, 2001Kriminski et al, 2002;Warkentin et al, 2006). Ice nucleation within protein crystals is strongly suppressed because the solvent is confined within a nanoporous network (Rault et al, 2003) and because much of the solvent is involved in hydrogen-bonding interactions with the protein.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, these temperatures are of the greatest interest for understanding radiation-damage mechanisms because near T = 200 K the protein and solvent system undergoes a dynamical/glass transition (Parak et al, 1982;Doster et al, 1989;Weik et al, 2001Weik et al, , 2004Weik et al, , 2005Gabel et al, 2002). The present study was made possible by the methods and observations described in detail by Warkentin & Thorne (2009), which were in turn inspired by earlier investigations (Weik et al, 2001(Weik et al, , 2005Juers & Matthews, 2001Kriminski et al, 2002;Warkentin et al, 2006). Ice nucleation within protein crystals is strongly suppressed because the solvent is confined within a nanoporous network (Rault et al, 2003) and because much of the solvent is involved in hydrogen-bonding interactions with the protein.…”
Section: Resultsmentioning
confidence: 93%
“…10 ml drops prepared by mixing 5 ml each of protein and well solution were suspended over 500 ml well solution. No penetrating cryoprotectants were added to the crystals at any temperature and a thorough wash in oil (as described in Warkentin & Thorne, 2009) was sufficient to obtain satisfactory cryocooling.…”
Section: Crystallizationmentioning
confidence: 99%
“…The possibility of performing slow-cooling experiments (Warkentin & Thorne, 2009) has already been discussed in x4. Comparing protein structures determined during slow cooling and during slow heating after flash-cooling might teach us more about the ensemble of conformational substates trapped in a flash-cooled crystalline protein.…”
Section: Perspectivesmentioning
confidence: 99%
“…In those cases, the viscosity of the mother liquor confined in the crystal is already sufficiently high to allow vitrification by flash-cooling. Recently, it has been reported that crystalline ice formation does not occur in thaumatin crystals without penetrating cryoprotectants when research papers the temperature is decreased from 300 to 100 K at a very slow rate (0.1 K s À1 ; Warkentin & Thorne, 2009). The potential interest of this new slow-cooling procedure in kinetic crystallography is discussed in x4.…”
Section: Temperature-dependent Behaviour Of Protein Crystalsmentioning
confidence: 99%
See 1 more Smart Citation